CONSTITUTIONAL TAX PRINCIPLES: FUNDAMENTAL GUARANTEES FOR THE TAXPAYER (CIPEEX, 2025)
This paper aims to present and discuss the main constitutional tax principles set forth in the 1988 Federal Constitution, analyzing their importance as taxpayer guarantees against the State's taxing power. The choice of this topic is justified by the principles' relevance in limiting State discretion, promoting tax justice and legal certainty. The study is based on bibliographical research, with doctrinal and normative analysis, particularly of Articles 145 to 150 of the Constitution. Among the principles addressed are: legality, prior notice, equality, taxable capacity, non-confiscation, and transparency. Each principle is examined in light of its protective function and its impact on the relationship between the tax authorities and taxpayers. The results indicate that compliance with these principles is essential to the legitimacy of the national tax system and the protection of citizens' fundamental rights, representing indispensable tools for controlling state action. The conclusion is that, despite formal guarantees, challenges remain in the practical implementation of these principles, especially due to flexible interpretations by administrative and judicial bodies. Therefore, strengthening jurisdictional oversight and tax education are fundamental measures for consolidating a fair and efficient tax system.